Association of hydroxysteroid 11-beta dehydrogenase 1 polymorphisms with chronic liver fibrosis and the occurrence of hepatocellular carcinoma in a Han Chinese population. Issue 1 (31st December 2022) - He, Xiuting; Wu, Jing; Hou, Wenli; Li, Jie; Xu, Hongqin
Abstract : In this study, we investigated the association of six single nucleotide polymorphisms (SNPs) in HSD11B1 with the progression of liver cirrhosis (LC) and occurrence of hepatocellular carcinoma (HCC) in a Han Chinese population. In this retrospective case–control study, a total of 656 ethnic Han Chinese patients with chronic hepatitis B virus infection were recruited. The clinicopathological characteristics of patients were obtained. This study group consisted of 104 patients with chronic hepatitis B, 266 patients with LC, and 286 patients with HCC. Six SNPs (rs846908, rs701950, rs846910, rs3753519, rs4844488, and rs932335) were genotyped using a MassArray system. Compared to the wild genotype GG, the CC genotype of rs932335 was significantly related to an increased risk of LC after adjusting for age, sex, smoking, and drinking (odds ratios = 7.89, 95% confidence interval: 1.04–60.06). Moreover, the CC genotype had increased serum levels of alanine transaminase and aspartate transaminase and elevated MELD scores in patients with LC. No significant differences were found among other SNPs. This study provides epidemiological evidence that the rs932335 variant of HSD11B1 may lead to the progression of LC and worse prognosis for patients with LC. No significant correlation was found between HSD11B1 genetic polymorphism and the progression of HCC.